Mitigation of liquefaction of saturated sand using biogas - He, J. (2013)
Some recent studies have indicated that the liquefaction potential of saturated sand can be greatly reduced if the sand can be made slightly unsaturated. One way to reduce the degree of saturation of sand is to inject gas into sand. This approach offers a cost-effective solution for mitigating liquefaction hazard over a large area. However, it is not easy to inject gas into sand in a uniform manner. A biogas method was developed in this study to overcome this difficulty. In this method, denitrifying bacteria are used to generate tiny, inert nitrogen gas bubbles in sand. Shaking table tests using a fully instrumented laminar box are conducted on both saturated sand and sand containing microbially generated nitrogen gas bubbles. Comparisons of the results of these tests indicate that the pore water pressure generated in the partially saturated sand was much smaller than that in saturated sand. Thus the proposed method is effective in reducing the liquefaction potential of sand.